2013
DOI: 10.1007/s11255-013-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction expression and the effects of gap junction inhibitors in overactive bladder models: does ovariectomy have a role?

Abstract: Ovariectomy had no effect on the gap junctions in the bladder and bladder overactivity alone. Therefore, obstruction is the main factor that increases the amount of gap junctions, and gap junction blockers are thus more effective in obstruction. However, ovariectomy was shown to decrease the expression of gap junctions and relaxation effect of gap junction blockers, when combined with BOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…29 In rats oxybutynin induced relaxant responses of partial BOO bladder 4 weeks postoperatively were significantly higher than in controls. 30 In cystitis we found that the responsiveness of detrusor muscle strips to CCh was decreased due to bladder wall thickening as a result of excessive build-up of type I collagen in the bladder. Our urodynamic recording, metabolic test and muscle strip contractility studies revealed that MK-801 treatment improved but could not completely reverse bladder function to the normal level.…”
Section: Discussionmentioning
confidence: 88%
“…29 In rats oxybutynin induced relaxant responses of partial BOO bladder 4 weeks postoperatively were significantly higher than in controls. 30 In cystitis we found that the responsiveness of detrusor muscle strips to CCh was decreased due to bladder wall thickening as a result of excessive build-up of type I collagen in the bladder. Our urodynamic recording, metabolic test and muscle strip contractility studies revealed that MK-801 treatment improved but could not completely reverse bladder function to the normal level.…”
Section: Discussionmentioning
confidence: 88%
“…To determine whether GJIC was required for the increase of adriamycin-induced cytotoxicity in cells with GJIC, the breast cancer cells Hs578T and MCF-7 were treated with chemical modulators of GJs prior and during exposure to 6 µM adriamycin [inhibitor, oleamide (22,23) or 18-α-GA (24,25); potentiator, RA (21,26)] at high density (GJ formed) or low density (no GJ formed). Fig.…”
Section: Influence Of Gj Potentiator On the Cytotoxicity Of Adriamycinmentioning
confidence: 99%
“…Gap junction blockers have previously been used on bladder tissue (Hashitani et al, 2001, 2004; Christ et al, 2003; Miyazato et al, 2006; Ikeda et al, 2007; Kim et al, 2011; Babaoglu et al, 2013). Similar effects have been found with 18α-GA and 18β-GA isomers (Miyazato et al, 2006; Ikeda et al, 2007; Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%